Delineating the roles of Co3O4 and N-doped carbon nanoweb (CNW) in bifunctional Co3O4/CNW catalysts for oxygen reduction and oxygen evolution reactions1. Issue 21 (7th June 2015) - Liu, Siyang; Li, Longjun; Ahn, Hyun S.; Manthiram, Arumugam
<x xml:space="preserve">Abstract</x> Carbon nanoweb (CNW) is the primary catalytic site for oxygen reduction reaction and Co3O4 is the primary catalytic site for oxygen evolution reaction in the Co3O4/CNW composite.